Processing Household Plastic Waste with the Pyrolysis Method into Fuel Oil in RW 03 Petir Village, Cipondoh, Tangerang - Puspawati, Catur; Andayani, Fitri; Maharani, Zulfia (Asian Journal of Pharmaceutical Research and Development, 2023)
Garbage is one of the wastes from human activities, which can have a negative impact on humans and the environment. Based on data from the Ministry of Industry regarding imports of plastic products, it can be predicted that the amount of waste that will arise. Imports of Poly Ethylene Terephthalate (PET) and Poly Propylene (PP) products continued to increase in line with the growth in chemical consumption. One alternative is converting plastic waste into fuel oil. Because basically plastic comes from petroleum, so it just needs to be returned to its original shape. Pyrolysis or devolatilization is a process of fractionating materials by temperature. Pyrolysis is the process of decomposing a material at high temperatures in the absence of air or with limited air. Oil from used plastic has unsaturated properties. This means that the ratio between carbon and hydrogen is not balanced so that there are links that are not filled. This pyrolysis oil is flammable, emits soot, and has a stimulating odor. This pyrolysis oil can be processed again so that it has saturated and stable properties. It is hoped that processing plastic into oil can provide an alternative solution to the plastic waste problem and can also provide alternative fuel solutions that can be used in society. The general objective of this study was to determine the quality of fuel oil from household plastic waste using the pyrolysis method. The population that will be studied in this study is plastic waste obtained from residents in the settlement of RW 03 Petir Village, Cipondoh, Tangerang, Banten. The sample to be examined in this study was used plastic waste with 2 kg of each type of plastic waste. The results of identifying the types of plastic waste found that the generation of plastic waste generated in RW 03 was 101.75 kg with the highest proportion being PET waste (70.33%) and the lowest being the Other category. Testing of the tool was carried out based on the design results, namely a simple household-scale pyrolysis tool that can be used to process Poly Ethylene Terephthalate plastic waste. Trials were carried out twice on 1 kg of plastic waste type Poly Ethylene Terephthalate, which produced oil as fuel. There are still many shortcomings in the tools that are made including the tool is still not ergonomic, there is no high voltage indicator tool and the tool is not portable so it is still difficult to move.